Evaluation of ocular biometry parameters before and after instillation of tropicamide 1.0%, phenylephrine 2.5% and combination of tropicamide 1.0%-phenylephrine 2.5% eye drops - Yee, Chong Soh (2018)
Introduction: The correct calculation of intra-ocular lens power is important for obtaining a high accuracy of postoperative refractive status. With that, the accuracy of the measurement of preoperative ocular biometry parameters (axial length, keratometry readings and anterior chamber depth) are important to obtain a precise IOL power to avoid postoperative refractive surprise. Topical dilating drops such as tropicamide and phenylephrine are widely used for pupil dilatation during an ocular examination and treatment. The mydriatic effect of the dilating eye drops might affect the ocular biometric parameters data which then can affect the final refractive outcome. Objective: The aim of our study was to evaluate the change in ocular biometry parameters before and after administration of tropicamide 1.0%, phenylephrine 2.5% and combination of tropicamide 1.0%- phenylephrine 2.5% eye drops. The secondary aim was to compare the mean difference of ocular biometry parameters between the groups.Methods: A randomised controlled trial study was conducted at Ophthalmology clinic, Hospital Universiti Sains Malaysia and Hospital Raja Permaisuri Bainun Ipoh from December 2015 to December 2017. The ocular biometric parameters (axial length, keratometric readings, anterior chamber depth) were obtained using noncontact partial coherence interferometer (IOL Master, Carl Zeiss, Germany) before and after the instillation of the dilating eye drops. Statistical analysis was done using Statistical Package for the Social Science, Version 22. Results: A total of 321 patients [group `1 (Tropicamide 1.0%): 107 patients, group 2 (Phenylephrine 2.5%): 107 patients, group 3 (Combination of Tropicamide 1% - Phenylephrine 2.5%): 107 patients] were recruited into this study. In group 1, the mean keratometry reading (P=0.028), keratometry 2 reading (P=0.028) and anterior chamber depth (P<0.001) were significantly different following pupil dilatation. In group 2, the mean keratometry reading (P=0.003), keratometry 2 reading (P=0.002), keratometry 1 and 2 axis (P=0.010) and anterior chamber depth (P<0.001) were significantly different between pre and post pupil dilatation. In group 3, the mean keratometry reading (P<0.001), keratometry 2 reading (P<0.001), keratometry 1 (P=0.008) and 2 axis (P=0.006), astigmatism power (P<0.001) and anterior chamber depth (P<0.001) were significantly different post pupil dilatation. Comparisons between the groups revealed statistically significant differences in the mean difference of keratometry 2 reading between group 1 and 3 [-0.049 (SD=0.228) diopters vs -0.143 (SD=0.195) diopters, P=0.004],group 2 and 3 [-0.036 (SD=0.207) diopters vs -0.143 (SD=0.195) diopters, P=0.017]. The keratometry 1 axis between group 1 and group 3 [1.065 (SD=11.252) ° vs -3.319 (SD=12.605) °, P=0.010] and keratometry 2 axis between group 1 and group 3 [1.075 (SD=11.252) ° vs -3.383 (SD=12.576) °, P=0.008] also showed statistically significant results. Meanwhile, the mean difference of anterior chamber depth also showed statistically significant difference between group 1 and 2 [-0.155 (SD=0.170) mm vs -0.070 (SD=0.086) mm, P=0.032], group 2 and 3 [-0.070 (SD=0.086) mm vs -0.127 (SD=0.108) mm, P=0.003] respectively. Conclusion: This study showed that the mean keratometry, keratometry 2 reading and anterior chamber depth were significantly different post pupil dilation in all three groups. Meanwhile the keratometry 1 and 2 axis were statistically significant different in group 2 and 3. The astigmatism power was significantly affected in group 3 only. The mean difference of keratometry 2 reading, keratometry 1 and 2 axis and anterior chamber depth in group 3 were significantly higher compared to the other two groups. Most of the ocular biometry parameters were significantly affected post pupil dilation, and especially in group 3. We suggest to defer measuring the ocular biometry parameters after pupil dilation, especially after instillation of combined tropicamide 1% and phenylephrine 2.5% eye drops. This is to avoid the unexpected refractive surprise post cataract surgery and to obtain the most accurate postoperative refractive status, especially for the precise correction of the astigmatism power and axis in toric lens.